Nutrient enrichment of fermented soybean tempeh via anaerobic fermentation with various biological activities - Mohd Yusof, Hamidah (2013)
Fermented soybean is found to contain increased level of bioactive contents such as proteins, polyphenolics, vitamins and minerals as a result of its microbial activity. Tempeh is an example of fermented soybean that has been recognized to have various health benefits contributed by the increased level of amino acids and antioxidants. Further enhancement of the bioactive properties of tempeh can be achieved via combination of anaerobic fermentation with selected strain of Rhizopus sp. as an innoculant. The purpose of this study is to determine and compare the cytotoxic,immunomodulatory, anti-inflammatory, liver ameliorative activities as well as acute toxicity of aqueous extract of nutrient enriched of soybean tempeh (NESTE) with nonfermented soybean (SBE). The production of NESTE involved by normal aerobic fermentation of tempeh followed by anaerobic fermentation using Rhizopus oligosporus (R. oligosporus) 5351 strain that was obtained from the culture collection of Malaysian Agricultural Research and Development Institute (MARDI). NESTE was produced by soaking soybeans for 18 h, steaming for 40 min, mixing with R. oligosporus 5351 strain starter culture prior to packaging with perforated plastic, incubating in aerobic condition for 30 h at 30 ˚C and continue incubating in anaerobic condition for 20 h at room temperature. Results have demonstrated that anaerobic fermentation on soybean had successfully produced NESTE, which contains 3210 ± 0.01 mg/ 100 g DW (dried weight) total free amino acids, 1100 ± 0.01 mg/ 100 g DW (dried weight) total essential amino acids and 338 ± 0.025 mg/ 100 g DW (dried weight) gamma-aminobutyric acid (GABA). Besides, NESTE also contains 42.64 ± 1.59 μg/ g extract of soluble phenolic acids and 22.56 ± 0.31 mg GAE/ g extract of total phenolic acids. These results indicated that the level of amino acids, GABA and antioxidants had significantly increased (p < 0.05). In addition, NESTE also inhibited the growth of MCF 7 cells in MTT assay with IC50 3.6 ± 0.22 mg/ mL after 72 h incubation while no cytotoxicity was detected in MCF 10A normal breast cell line. Cell cycle with flow cytometry analysis illustrated that NESTE arrested MCF 7 cells at G0/G1 phase. Furthermore, increment of the cell population in sub G0/G1 has shown that IC50 of NESTE at 72 h was able to induce the best apoptotic effect towards MCF 7 cells. Annexin V-FITC/PI assay has further confirmed the apoptotic effect induced by NESTE on MCF 7 cells where substantial amount of early apoptotic cells were detected. On the other hand, the immunomodulatory study of NESTE has shown that NESTE stimulated splenic cells proliferation in time and dosage dependent manner which can be observed through MTT and BrdU assays. Additionally, NESTE was also able to stimulate and enhance cytokine secretion (IL-2 and IFN-gamma) in time and dosage dependent manner.Antiinflammatory study has shown that NESTE exhibited no sign of cytotoxicity towards RAW 264.7 cells (macrophage cells) and was able to suppress the level of nitric oxide,which is an inflammatory indicator. In vivo tests on mice ear edema and analgesic demonstrated that the best effect was achieved when treated with 1000 mg/ kg of NESTE suggesting that NESTE was able to suppress the edematous effect of mice ear and produce better and lasting analgesic effect. The evaluation of in vivo liver ameliorative activity of NESTE indicated that NESTE could revert the effect of steatosis in hepatocytes to normal condition, increase the antioxidant level and reduce the inflammation of the ethanol treated mice. Moreover, NESTE exhibited no sign of toxicity towards mice up to 5000 mg/ kg. Overall, anaerobic fermentation of soybean using R. oligosporus sp. 5351 strain has successfully produced NESTE with higher bioactive contents such as GABA, amino acid and antioxidants. This finding suggested that NESTE could be formulated as a healthy food supplements that possessed the anticancer, immunomodulatory, anti-inflammatory and liver ameliorative effect.